Family Communication in the Community of Siring Agung Village, Palembang in Shaping Children's Characters in the Digital Era - Ceindy Paiza Yuliani; Heri Junaidi; Chairunnisah Putri Ayu Ningsih (Universitas Muhammadiyah Palu, 2026)
his study aims to find out the character of children in the family of the people of Siring Agung Village Palembang in the digital era through observation of attitudes, behaviors, and daily habits, as well as explain the role of family communication in shaping character through communication patterns, parenting, supervision, and direction in the use of digital technology. The digitalization phenomenon triggers changes in family interaction patterns, where the uncontrolled use of gadgets has the potential to reduce the quality of direct communication between parents and children and affect children's discipline and responsibility. This study uses a qualitative method with a descriptive approach, through observation and in-depth interviews with 10 informants of parents and children in Siring Agung Village, Ilir Barat I District, Palembang City. The theoretical basis used is Family Communication Patterns Theory by Ascan F. Koerner and Mary Anne Fitzpatrick which focuses on conversation orientation and conformity orientation. The results of the study show that the formation of children's character is directed at the values of discipline, responsibility, openness, good manners, and the ability to understand the limits of digital media. Discipline and good manners are formed through screen time rules and parental examples, while responsibility and openness are built through persuasive and supportive two-way communication. Through adaptive interpersonal communication, parents play the role of the main guide in minimizing the negative impact of technology in order to optimize children's moral development.